The spread of Keynesian economics: a comparison of the Belgian and Italian experiences - Ivo Maes (National Bank of Belgium, 2007)
Keynesian economics dominated economic thought and macroeconomic policy-making in the 1950s and 1960s. However, the diffusion of Keynesian economics has been uneven. In this paper, we compare the spread of Keynesian economics in two continental European countries: Belgium and Italy. We focus on the post-World War II period, taking as the main message of Keynesian economics that the market is inherently unstable and that the government has a key role in economic life in steering effective demand. We further follow Coddington's distinction between "hydraulic", "disequilibrium" and "fundamentalist" Keynesianism. The study shows that Belgium and Italy were two countries were Keynesian economics gained ground only relatively late. The breakthrough of (hydraulic) Keynesianism came in areas which were close to the policy-making process: setting up national income accounts, the construction of macroeconomic models and correcting regional imbalances. The main difference between the two countries was the strong position of fundamentalist Keynesianism in the academic world in Italy, while in Belgium, disequilibrium Keynesianism was more influential.
Keywords: B22; E60; 330; Keynesian economics; Belgium; Italy; macroeconomic policy-making; Keynesianismus; Wirtschaftspolitik; Wirtschaftswachstum; Ökonomische Ideengeschichte; Geschichte; Belgien; Italien